Human trafficking for the purpose of organ removal : a human rights based perspective - Tunde-Yara, Faith (Department of Public Law, 2016)
Human trafficking for the purpose of organ removal, known to be an obscure and uncommon form of trafficking in persons, has since become a popular phenomenon across various countries of the world. The crime is recognized in the Protocol to Prevent, Suppress and Punish Trafficking in Persons, especially women and children, which supplements the United Nations Convention against Transnational Organized Crime. A reason for the inclusion of this form of trafficking in this particular international instrument on transnational organized crime is because most forms of trafficking, and more particularly human trafficking for the purpose of organ removal, as well as organ trafficking are generally perpetrated by transnational organized criminal groups. This dissertation seeks to consider the crime in detail, from a human right-based approach. This approach acknowledges that trafficking in all its forms, is a violation of human rights and seeks to depart from the common debates surrounding the spread of organ trafficking over the years. A large proportion of these debates have attributed the shortage of organs to the spread of the organ black market and organ trafficking in general. These debates have therefore focused on addressing the shortage of organs by developing systems to promote altruistic donation of organs. Even though there is an international recognition and admittance of the fact that human trafficking for the purpose of organ removal constitutes a serious human right abuse, there is still a wide gap in the body of research that focuses on the human right abuses involved in this type of human trafficking, and the need to protect and promote the rights of victim-donors. The aforementioned gap will serve as the crux of this dissertation as efforts will be made to address the inherent human rights abuses that victim-donors face. This dissertation will begin by introducing the crime of human trafficking through a brief historical overview. It will then proceed to give a background information on human trafficking for the purpose of organ removal. Subsequent chapters will address in detail the trends and patterns of the crime, the modus operandi of organ traffickers, the role players in organ trafficking networks, the consequences of the crime on the victims involved, the inherent human right violations promoted through the continuous perpetration of the crime of human trafficking for the purpose of organ removal, and the responses that have been given to curbing the crime from different international, regional and national institutions. Case studies will be examined to buttress the facts and findings of the entire dissertation.